2022
DOI: 10.1021/acsestengg.2c00220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Nutrient Doses on Biostimulation of Petroleum Hydrocarbon Biodegradation in Cold Region Soils

Abstract: Biostimulation by addition of nitrogen (N) and phosphorus (P) for enhancement of biodegradation of petroleum hydrocarbons in contaminated soils is a common practice in sub-Arctic (cold) regions. Based on the data reported in 58 peerreviewed papers on hydrocarbon degradation in northern region soils, there was no identifiable optimal nutrient dose, although applied doses ranged over 3 orders of magnitude. Microcosm slurry biodegradation experiments conducted over a range of N (41 to 1350 mg/kg) and P (46 and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In those samples, the prokaryotic alpha-diversity was strongly associated with salinity, temperature and organic carbon content (Jeanbille et al 2016). Additionally, nutrient availability is a key factor for increasing microbial biomass and promoting hydrocarbon degradation (Ortmann et al 2019;Bianco et al 2020;Fragkou et al 2021;Ellis et al 2022;Kundu et al 2022;Michel et al 2022). Contrary to the results for the tidal flat in this study, several studies demonstrated nutrient addition significantly enriched hydrocarbon degraders and enhanced biodegradation rate (Chang et al 2010;Kim et al 2018;Bianco et al 2020;Ellis et al 2022).…”
Section: Cell Densitymentioning
confidence: 99%
“…In those samples, the prokaryotic alpha-diversity was strongly associated with salinity, temperature and organic carbon content (Jeanbille et al 2016). Additionally, nutrient availability is a key factor for increasing microbial biomass and promoting hydrocarbon degradation (Ortmann et al 2019;Bianco et al 2020;Fragkou et al 2021;Ellis et al 2022;Kundu et al 2022;Michel et al 2022). Contrary to the results for the tidal flat in this study, several studies demonstrated nutrient addition significantly enriched hydrocarbon degraders and enhanced biodegradation rate (Chang et al 2010;Kim et al 2018;Bianco et al 2020;Ellis et al 2022).…”
Section: Cell Densitymentioning
confidence: 99%
“…Furthermore, through studies of soil microbial evolution, it has been shown that biostimulation ensures soil microbial uniformity and diversity, allowing for more efficient hydrocarbon degradation (Wu et al, 2019). It was also shown that in soils contaminated with petroleum hydrocarbons there was an enrichment of degrading microorganisms of the Pseudomonadaceae and Burkholderiaceae bacterial families, based on 16S rRNA sequencing of DNA analysis (Kundu et al, 2022).…”
Section: Biostimulationmentioning
confidence: 99%